Motherhood and the Cost of Job Search - Arnaud Philippe; Daphné Skandalis (Institute of Labor Economics (IZA), 2023)
Why do women experience a persistent drop in labor earnings upon becoming mothers, i.e. a "child penalty"? We study a new mechanism: search frictions. We analyze data on job applications sent on a popular online platform linked with administrative data for 350,000 involuntarily unemployed workers in France. First, we highlight differences in job search behavior between mothers and similar women with no children. Mothers send 12.2% fewer job applications and are more selective regarding wage and non-wage amenities. Consistently, they have a lower job finding rate. Second, we analyze the exact time when applications are sent and highlight differences in the timing of job search. We find that mothers' rate of applications decreases by 20.3% in the hours and days when there is no school. We also show that mothers responded to a reform that introduced school on Wednesday by smoothing their search across weekdays and narrowing their search timing gap with other women. In a simple search model, we show that our results imply that mothers both face lower incentives and higher costs to search. We conclude that search frictions disproportionately prevent mothers from improving their labor market situation and contribute to the child penalty.
Keywords: J16; J22; J64; 330; job search; gender inequality; time allocation; child penalty